ANALISIS SIFAT FISIKO KIMIA SAUS CABAI FORTIFIKASI LABU SIAM DAN LABU KUNING - Indrawati, Sriwulan; Lahming, Lahming; Sukainah, Andi (Universitas Negeri Makassar, 2018)
The purpose of this study was to determine the effect of adding chili and pumpkin concentration to the physicochemistry properties of chili pepper sauce. This research is an experimen research with a complete RandomizedÂ Design of factorial pattern consisting of two factors: flask type (squash siam and yellow squash) and concentration of chili (40%, 50% and 60%). Research variables observed were viscosity, ash content, vitamin C, pH and organoleptic test including color, aroma, taste, and texture. Analyze technique in this research is the of analysis variety by using SPSS version 23. The result of research shows that the best treatment is the use of yellow squash with 60% chili concentration. namely of viscosity (2.54%), ash content (6.41%) , vitamin C (221.67%), pH (2.20%), color (3.95%), flavor (3.65%) and aroma (3.59%) texture (3.52%) the resulting sauce.